A Study on the Stiffness of Solid And Hollow Section Brass - Vinod A/L Chandra Sayakaran, Vinod (Universiti Teknologi Petronas, 2010)
Brass is an alloy of copper and zinc, with varieties of proportion yielding different types of brasses. Alpha brass is a high purity cold forming brass used in handrails, grillwork and radiator cores, with excellent suitability for brazing, soldering and cold-working. This project aimed to study the differences in stiffness of solid and hollow section brass components. A three-point bending test was performed to evaluate the stiffness of brass specimens, after which the specimen was fractured and examined using a Scanning Electron Microscope (SEM). The specimens were 6mm square sections with a span of 120mm, where the hollow specimen had a 4mmdiameter hole in the middle.